Development of an algorithm for identifying the autism spectrum based on features using deep learning methods - Amirbay, Aizat; Mukhanova, Ayagoz; Baigabylov, Nurlan; Kudabekov, Medet; Mukhambetova, Kuralay; Baigusheva, Kanagat; Baibulova, Makbal; Ospanova, Tleugaisha (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The presented scientific work describes the results of the development and evaluation of two deep learning algorithms: long short-term memory with a convolutional neural network (LSTM+CNN) and long short-term memory with an autoencoder (LSTM+AE), designed for the diagnosis of autism spectrum disorders. The study focuses on the use of eye tracking technology to collect data on participants' eye movements while interacting with animated objects. These data were saved in NumPy array format (.npy) for ease of later analysis. The algorithms were evaluated in terms of their accuracy, generalization ability, and training time, which was confirmed by experts. The main goal of the study is to improve the diagnosis of autism, making it more accurate and effective. The convolutional neural network long short-term memory and autoencoder-long short-term memory models have shown promise as tools for achieving this goal, with the autoencoder model standing out for its ability to identify internal relationships in data. The article also discusses potential clinical applications of these algorithms and directions for future research.